2018
DOI: 10.1080/14685248.2018.1461875
|View full text |Cite
|
Sign up to set email alerts
|

Advanced lattice Boltzmann scheme for high-Reynolds-number magneto-hydrodynamic flows

Abstract: To cite this version:Alessandro de Rosis, Emmanuel Lévêque, Robert Chahine. Advanced lattice Boltzmann scheme for high-Reynolds-number magneto-hydrodynamic flows.ABSTRACT 11 Is the lattice Boltzmann method suitable to investigate numerically 12 high-Reynolds-number magneto-hydrodynamic (MHD) flows? It is shown 13 that a standard approach based on the Bhatnagar-Gross-Krook (BGK) collision 14 operator rapidly yields unstable simulations as the Reynolds number increases. In 15 order to circumvent this limitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…As a consequence, we proved that it is possible to derive central-moments-based schemes for a broad range of governing equations, as preconditioning [37] and shallow water equations [38]. A compelling proof of the generality of the algorithm is provided in [39], where a central-moments-based scheme able to recover the solution of the incompressible Navier-Stokes equations for magnetohydrodynamics has been derived. If one compares the algorithm outlined in [39] with the nonconductive case [33], it is possible to appreciate that the structure of the algorithm is identical.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…As a consequence, we proved that it is possible to derive central-moments-based schemes for a broad range of governing equations, as preconditioning [37] and shallow water equations [38]. A compelling proof of the generality of the algorithm is provided in [39], where a central-moments-based scheme able to recover the solution of the incompressible Navier-Stokes equations for magnetohydrodynamics has been derived. If one compares the algorithm outlined in [39] with the nonconductive case [33], it is possible to appreciate that the structure of the algorithm is identical.…”
Section: Introductionmentioning
confidence: 88%
“…A compelling proof of the generality of the algorithm is provided in [39], where a central-moments-based scheme able to recover the solution of the incompressible Navier-Stokes equations for magnetohydrodynamics has been derived. If one compares the algorithm outlined in [39] with the nonconductive case [33], it is possible to appreciate that the structure of the algorithm is identical. The only difference lies in the equilibrium central moments, that are enriched by terms accounting for the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Its simulation represents a hard task since smaller and smaller structures appear in the domain as the Reynolds number grows. This test case is then a perfect candidate to assess (1) the accuracy of the present method to capture the existence of fine flow features, as well as ( 2) its ability to deal with high local gradients that arise during the simulation 66 .…”
Section: Two-dimensional Orszag-tang Vortexmentioning
confidence: 99%
“…Consequently, the proposed approach allows the derivation of CM-LBMs for any lattice of discrete velocities in a straightforward manner. This was thoroughly demonstrated by successfully recovering different sets of governing equations with this approach, hence allowing the simulation of a rich variety of physics problems such as shallow waters 65 , magnetohydrodynamic 66 , and multicomponent flows 67 among others.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was demonstrated that it is possible to adopt a CMs-based procedure where moments relax to whatever discrete equilibrium state and for whatever lattice discretization [22][23][24][25][26] . It is possible to switch from populations to CMs (and vice versa) by simply multiplying (or dividing) by a transformation matrix that depends on the adopted lattice and the local fluid velocity.…”
mentioning
confidence: 99%